Oil Shocks and Stock Prices of Airlines - An East Asia Perspective - Lee, Pau Boon (2005)
The aim of this dissertation is to study and analyse the impact of oil price shock on the share prices of airline companies in East Asia, in particular international air carriers from Japan, Hong Kong, South Korea, Singapore and Malaysia by looking at how the companies‘ share prices respond to the news of oil shocks. The companies involved in this study were Japan Airlines ("JAL"), All Nippon Airways ("ANA"), Cathay Pacific Airways ("Cathay"), Korean Air ("KAL"), Malaysian Airlines ("MAS") and Singapore Airlines ("SIA"). The time period covered in this study was from the year 1973 to year 2004. In view that investors‘ perception of future earnings of a company and its risk level are reflected in the stock prices, a company‘s stock price will increase or decrease, depending on how investors perceive an event will affect the company‘s value (Wells, 2004). In addition to studying the reaction of airlines‘ stock prices to the news of oil shock, it is also the aim of this dissertation to examine whether the airline companies under consideration over or under-perform their respective stock markets.